2013
DOI: 10.1103/physrevlett.111.226802
|View full text |Cite
|
Sign up to set email alerts
|

Space-Charge Transfer in Hybrid Inorganic-Organic Systems

Abstract: We discuss density functional theory calculations of hybrid inorganic-organic systems that explicitly include the global effects of doping (i.e., position of the Fermi level) and the formation of a space-charge layer. For the example of tetrafluoro-tetracyanoquinodimethane on the ZnO(0001[over ¯]) surface we show that the adsorption energy and electron transfer depend strongly on the ZnO doping. The associated work function changes are large, for which the formation of space-charge layers is the main driving f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 49 publications
5
125
0
Order By: Relevance
“…Hybrid density functional methods have been recently benchmarked and successfully applied in several computational investigations on hybrid ZnO/organic materials and interfaces. [35][36][37][38] We derived explicit atomistic structural models for the ZnO:HQ superlattices starting from bulk ZnO. Bulk ZnO crystallizes in the hexagonal wurtzite structure with four atoms in the primitive cell (space group P6 3 mc).…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Hybrid density functional methods have been recently benchmarked and successfully applied in several computational investigations on hybrid ZnO/organic materials and interfaces. [35][36][37][38] We derived explicit atomistic structural models for the ZnO:HQ superlattices starting from bulk ZnO. Bulk ZnO crystallizes in the hexagonal wurtzite structure with four atoms in the primitive cell (space group P6 3 mc).…”
Section: Structural Propertiesmentioning
confidence: 99%
“…This space-charge region can affect the charge-transport properties across the interface and significantly weakens the binding between substrate and adsorbate. [8] The spatial extent and the magnitude of the band bending depend on the amount of charge-transfer from the bulk to the adsorbate as well as on the bulk doping concentration and profile. Experimentally, those parameters are often challenging to control and not always well known.…”
mentioning
confidence: 99%
“…The relative contribution of ΔΦ BB and ΔΦ SD depends strongly on the doping concentration of the substrate. [8] In principle, for low doping concentrations and strong electron acceptors, band bending could be as large as the total band gap of the substrate (≈3.5 eV in ZnO). In practice, however, ΔΦ BB is almost always limited by the presence of defect states at or near the surface, such as oxygen vacancies, [11][12][13] provided they are present in sufficient concentrations.…”
mentioning
confidence: 99%
“…In a recent work, Greiner et al 10 analyzed a variety of non-reactive oxide/organic interfaces and concluded that the energy level alignment is determined mainly by one driving force: the electron chemical potential equilibration between the oxide Fermi level and the organic ionization energy. On the other hand, Xu et al 11 have conclusively shown that a second driving force is the oxide doping and the concomitant formation of a space-charge layer upon the interaction with the organic material; for strongly n-doped oxides, such as ZnO or TiO 2 , this mechanism is particularly important when the organic affinity level is located below the oxide Fermi level, as is the case of F4TCNQ physisorbed on a H-saturated ZnO(000-1)surface. 11 Recently, other groups 6,12 have also shown the important role that the oxide/organic interface chemistry has in the barrier formation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Xu et al 11 have conclusively shown that a second driving force is the oxide doping and the concomitant formation of a space-charge layer upon the interaction with the organic material; for strongly n-doped oxides, such as ZnO or TiO 2 , this mechanism is particularly important when the organic affinity level is located below the oxide Fermi level, as is the case of F4TCNQ physisorbed on a H-saturated ZnO(000-1)surface. 11 Recently, other groups 6,12 have also shown the important role that the oxide/organic interface chemistry has in the barrier formation. All this suggests that the injection of charge between transition metal oxides and organic materials depends crucially on the interface barrier that is determined mainly by the relative electronegativity of both materials, the possible spacecharge layer formed in the oxide, and the chemical interaction between the oxide and the organic.…”
Section: Introductionmentioning
confidence: 99%